2014
DOI: 10.3109/0142159x.2014.956058
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Korean medical students: Findings from a nationwide survey

Abstract: The JSE score of Korean medical students was lower than that of students in Western countries. The difference of gender and medical school admission system should be considered, and capability to apply empathy to clinical practice should be focused upon in medical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
84
6
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 23 publications
15
84
6
6
Order By: Relevance
“…In this study, we found that women were more empathic than men, which concurs with studies in most other countries [5,9,16,21], and in particular, with a study of students studying a five-year medical training program in northern China [19]. However, there was no gender difference in empathy in a previous study of Chinese medical students studying an eight-year program [7].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found that women were more empathic than men, which concurs with studies in most other countries [5,9,16,21], and in particular, with a study of students studying a five-year medical training program in northern China [19]. However, there was no gender difference in empathy in a previous study of Chinese medical students studying an eight-year program [7].…”
Section: Discussionsupporting
confidence: 91%
“…The mean empathy score of the sample in the present study is similar to that found in Japan [5], China [7], Korea [9], India [10], and Iran [11] and relatively lower than the mean scores reported in some Western countries, such as Spain [12], America [13], and Germany [14]. Thus, Asian students tend to have similar levels of empathy but lower than do Western students (Additional file 1: Table S1 in Supplemental Data).…”
Section: Discussionsupporting
confidence: 79%
“…For example a study among Chinese medical students revealed a total score of 109.6±12.09 (Wen et al 2013) whereas another study from Iran found a score of 105.1±12.9 (Rahimi-Madiseh et al 2010). Studies in Korea (Roh et al 2010;Park et al 2015), Japan (Kataoka et al 2009), and Kuwait (Hasan et al 2013) found similar total empathy scores like ours.…”
Section: Discussionsupporting
confidence: 71%
“…confined and unique to a more limited locality) contextual facets may explain the conflicting patterns in empathy change demonstrated by certain studies within the same country or region (e.g. certain studies within a given country, such as the USA or South Korea) that produce a pattern of empathy change that differs from that shown by the rest of the studies carried out within the same country (e.g. the USA and South Korea).…”
Section: Discussionmentioning
confidence: 99%
“…However, the interplay between the general and specific contextual facets can be used to explain some of the findings of this review. For example, of the four South Korean studies, the only one to produce evidence of a significant decrease in empathy over the undergraduate years was a large, countrywide, cross‐sectional study, whereas the other three were comparatively smaller (but with large enough sample sizes) school‐based studies and one was a longitudinal study. It is very likely that the countrywide study showed a negative change (i.e.…”
Section: Discussionmentioning
confidence: 99%